Theorizing about accreditation optimal model of higher education system in Iran based on of grounded theory - mohammad mojtabazadeh; عباس عباس پور; حسن ملکی; مقصود فراست خواه (Allameh Tabataba'i University Press, 2016)
This study aimed to identify factors affecting the model of accreditation and quality assurance of higher education in Iran. the study was conducted using qualitative research through grounded theory. the study population had higher education experts, which 36 persons by purposive sampling for semi-structured interview were selected. in addition to interview, 3 other sources were used to collect data, which are, observing, taking notes and documents. for this purpose, data obtained from interviews, observations, notes and documents were converted into text data. after that, we act the first to open coding, then, to have axial and selective action. in axial coding stage, 25 core categories were determined. in selective coding stage, all major categories and core categories in terms of condition, interactive / process and outcome characteristics was classified. in the end, category of quality discourse, fear and hope, as the most original and the most ultimate core category select and according to its features were developed. then, related made other categories in the form of a paradigm model with the this category.